2016
DOI: 10.3906/vet-1601-113
|View full text |Cite
|
Sign up to set email alerts
|

The determination of in vitro gas production and metabolizable energy value of rice straw treated with exogenous fibrolytic enzymes

Abstract: Chemical analyses and in vitro gas production techniques were conducted in the Ruminant Feed Evaluation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
2
4
0
1
Order By: Relevance
“…These results are in line with those obtained by Salem et al (2013), who reported that fibrolytic enzymes can increase total SCFA concentrations. Similar notable increases were found in the same parameters by Selçuk et al (2016), thus providing more evidence for positive correlations between in vitro OMD, the amount of gas released and ME during fermentation. However, López et al (2013) and Beauchemin et al (2003) reported that suitable fibrolytic enzymes can improve fermentation efficiency, thus increasing metabolized energy, particularly when the substrate is made of fibre-rich material and is limited in nutrient energy.…”
Section: Methane Production Ruminal Fermentation and Kinetic Measuresupporting
confidence: 73%
See 1 more Smart Citation
“…These results are in line with those obtained by Salem et al (2013), who reported that fibrolytic enzymes can increase total SCFA concentrations. Similar notable increases were found in the same parameters by Selçuk et al (2016), thus providing more evidence for positive correlations between in vitro OMD, the amount of gas released and ME during fermentation. However, López et al (2013) and Beauchemin et al (2003) reported that suitable fibrolytic enzymes can improve fermentation efficiency, thus increasing metabolized energy, particularly when the substrate is made of fibre-rich material and is limited in nutrient energy.…”
Section: Methane Production Ruminal Fermentation and Kinetic Measuresupporting
confidence: 73%
“…Similar notable increases were found in the same parameters by Selçuk et al . (2016), thus providing more evidence for positive correlations between in vitro OMD, the amount of gas released and ME during fermentation. However, López et al .…”
Section: Methane Production Ruminal Fermentation and Kinetic Measurementioning
confidence: 98%
“…The average ADL was in the range of 41 g/kg to 51 g/kg. Although this figure is lower than the 43 to 69.7 g/ kg reported by Rahman et al (2010), the present results confirm the high lignocellulosic content of rice straw as reported by other studies (Hadizadeh et al, 2015;Selcuk et al, 2016;Sheikh et al, 2017;Van Soest, 2006). The fact that Angola rice straw had the least cellulose content implies that it is the better digestible straw.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies in other countries have indicated that rice straw contains about 900.0-954.9 g/ kg dry matter, 50-120 g/kg lignin, 30-59.6 g/kg crude protein, 298-370 g/kg crude fibre, 1.4-10 g/ kg crude fat, 0.2-1.6 g/kg phosphorus, 1.4-5.5 g/kg calcium, 44% total digestible nutrients, 7.95 MJ/kg of digestible energy, 80-158 g/kg silica and high oxalates conferring poor digestibility (Singh et al, 1995;Van Soest, 2006;Hadizadeh et al, 2015;Ansah et al 2017) and in some cases toxicity (Bakshi & Wadhwa, 2017;.Drake et al, 2002). Notwithstanding its role as a livestock feed resource in many developing countries, rice straw is rich in polysaccharides on one side, and a high level of lignin conferring it poor nutritive value due to poor digestibility and palatability on the other side (Malik et al, 2015;Selcuk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Semakin tinggi nilai ADF, maka kualitas daya cerna hijauan makanan ternak semakin rendah (Crampton and Haris, 1969 Yanuarianto et al (2015) di Mataram menunjukkan kandungan ADF jerami padi sebesar 52,01%, sedangkan asal Jawa Tengah menunjukkan nilai sebesar 60,57% (Anam et al, 2012). Penelitian kandungan ADF jerami padi asal Thailand oleh Wanapat et al (2013) menunjukkan nilai sebesar 63,7% dan asal Turki sebesar 41,15% (Selçuk et al, 2016). Kandungan ADF yang cukup rendah yaitu 40,95% ditunjukkan oleh hasil penelitian jerami padi di Cina (Yuan et al, 2016).…”
Section: Nilai Nutrisi Jeramiunclassified